1992
DOI: 10.1139/o92-166
|View full text |Cite
|
Sign up to set email alerts
|

Zygote giant cell differentiation in Dictyostelium discoideum: biochemical markers of specific stages of sexual development

Abstract: Sexual development in Dictyostelium discoideum has many unique features making it an attractive eukaryotic model system for the study of biomembrane fusion and intercellular communication. The work presented here provides primary biochemical evidence for two distinct phases during early sexual development that appear to be defined by calcium-dependent gamete cell fusion. In addition, we introduce a novel procedure for the enrichment of zygote giant cells and use this method to define certain wheat-germ aggluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…This hypothesis is consistent with the thick glycocalyx present at the cell surface of the amoebae, poor conservation of the gp130-polypeptide sequence in related species as reported here, and evidence for extensive N-glycosylation differences among different social amoebae . Previous studies of D. discoideum have implicated glycoproteins and oligosaccharide moieties in cell adhesion, phagocytosis and sexual development. Classical methods and a recent mass spectrometry-based study describe major features of the D. discoideum N-glycome, but it is not known which are presented at the cell surface. Here we apply a mass spectrometry-based approach to analyze the N-glycans on a secreted recombinant version of gp130.…”
Section: Introductionsupporting
confidence: 85%
“…This hypothesis is consistent with the thick glycocalyx present at the cell surface of the amoebae, poor conservation of the gp130-polypeptide sequence in related species as reported here, and evidence for extensive N-glycosylation differences among different social amoebae . Previous studies of D. discoideum have implicated glycoproteins and oligosaccharide moieties in cell adhesion, phagocytosis and sexual development. Classical methods and a recent mass spectrometry-based study describe major features of the D. discoideum N-glycome, but it is not known which are presented at the cell surface. Here we apply a mass spectrometry-based approach to analyze the N-glycans on a secreted recombinant version of gp130.…”
Section: Introductionsupporting
confidence: 85%
“…Browning et al recently identified gpl30, a WGA-binding glycoprotein that was detected in association with the sexual development of D. discoideum (30,31). Although this protein and DdFRP3 are similar in that both have WGA-binding sugar chains and the same molecular mass, we do not consider them to be identical, for the following reasons.…”
Section: Discussionmentioning
confidence: 91%
“…First, their expression levels are different; the former is detected while the latter is not detected by the lectin staining. Second, their expression period is different; GP138B is expressed in vegetative cells (13), while the gpl30 identified by Browning et al is expressed after cell fusion (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Further, an analysis using Western blotting has shown that a glucosylated receptor appearing at the onset of phagocytosis, has a molecular weight of about 126 kDa (gp 126). A WGA-binding glycoprotein appearing at about the same time had a molecular weight of 130 kDa (gp130) and may be the same receptor [8]. It is interesting to speculate whether the gp126 receptor implicated in nonspecific phagocytosis in vegetative amoebae is the same as that found during sexual phagocytosis [8,42).…”
Section: Discussionmentioning
confidence: 99%
“…A WGA-binding glycoprotein appearing at about the same time had a molecular weight of 130 kDa (gp130) and may be the same receptor [8]. It is interesting to speculate whether the gp126 receptor implicated in nonspecific phagocytosis in vegetative amoebae is the same as that found during sexual phagocytosis [8,42). However, there are indications that this may not be the case.…”
Section: Discussionmentioning
confidence: 99%